Renal transplantation: Opportunities and risks for medical refugees - Mammadova, Dilbar; Hirsch, K.; Schwaiger, Brigitte; Wullich, Bernd; Rascher, Wolfgang (Urologe, 2018)
BACKGROUND: Families with children and adolescents with end-stage renal disease came to Germany from the former Eastern Bloc countries before the wave of refugees in 2015, in order to enable their children to survive with adequate kidney replacement therapy and in the best case a kidney transplant. METHODS: In a case study, medical records of 4 childen and adolescents were retrospectively analyzed. These patients who fled to Germany for the treatment of terminal renal failure applied for asylum and were successfully transplanted after the usual waiting period. RESULTS: Four of the eight children and adolescents who came to Erlangen for treatment of terminal renal failure between 2003 and 2013 received a functioning kidney transplant (deceased donor kidney) after dialysis therapy was difficult due to lack of compliance to drug and dietary recommendations such as fluid restriction. Since children and adolescents are treated with chronic dialysis only with the aim of kidney transplantation, a living donation was discussed but was not possible for medical reasons. 3 recipients are symptom-free with a functional graft. DISCUSSION: The case study demonstrates that children and adolescents fleeing to Germany due to their end stage renal disease are better integrated after kidney transplantation, have better chances of obtaining a good education and can be expected to live independently with their own income in the future.
EVALuna2:35726